Characteristics of anchoveta (Engraulis ringens) schools in the optimum zone and the physiological stress zone of its distribution between 2011 and 2021. (27th June 2022) - Castillo, Pedro Ramiro; Peña, Cecilia; Grados, Daniel; La Cruz, Luis; Valdez, Carlos; Pozada‐Herrera, Marissela; Cornejo, Rodolfo
Abstract: This study has considered anchoveta acoustic data from the Pelagic Resources Hydroacoustic Assessment Surveys carried out by the Peruvian Sea Institute (IMARPE) and free access satellite data (HYCOM and MODIS from the USA) of some oceanographic variables between the period 2011 and 2021, to know the oceanographic conditions, characteristics of schools and size structure in the optimum zone (OZ) and in the physiological stress zone (PSZ), of their total distribution. The OZ is determined by the extent of the Cold Coastal Waters (CCW), and the PSZ is determined by the mixing of waters, to the north by the CCW‐ESW (Equatorial Surface Waters) and to the west between the CCW‐SSW (Subtropical Surface Waters). The range of sea surface temperature and salinity in the PSZ (16.1–25.0°C and 34.65–35.29, respectively) was wider than in the OZ (14.5–24.0°C and 34.65–35.20, respectively), where a higher number of schools were recorded. Our analyses showed that the morphometric and energetic acoustic descriptors of anchoveta schools in the summer were higher during summers compared to springs. In terms of positional characteristics, the mean depth of the schools in the PSZ was slightly greater than in the OZ. The total size structure of anchoveta in the OZ consisted mainly of juvenile specimens (less than 12 cm total length) in the summer of 2011 and 2013–2014 and in the spring between 2014–2017 and 2021. In the PSZ, adult specimens (greater than 12 cm total length) predominated in summer between 2011–2013, 2015, 2018, and 2021 and in spring between 2011–2013, 2015, and between 2018–2021. However, specimens greater than 10 cm in total length were found in the PSZ. Knowledge of the location of this zone away from the coast will allow a high probability of anchoveta capture of adult specimens during fishing periods.